Probable Sarcopenia, Obesity, and Risk of All-Cause Mortality: A Pooled Analysis of 4,612 Participants - Sääksjärvi Katri; Härkänen Tommi; Stenholm Sari; Schaap Laura; Lundqvist Annamari; Koskinen Seppo; Borodulin Katja; Visser Marjolein (KARGER, 2025)
Introduction: Conflicting evidence exists concerning whether having sarcopenic obesity has additive mortality risk over having only sarcopenia or obesity. We examined the independent and combined associations of obesity and probable sarcopenia with all-cause mortality.
Methods: The pooled analysis included three large, harmonized datasets (Health 2000 Survey; Health, Aging and Body Composition Study; Longitudinal Aging Study Amsterdam) with mortality follow-up data on individuals aged 70 years and over at baseline (n = 4,612). Obesity indicators included body mass index and waist circumference, and probable sarcopenia was defined based on grip strength. The mixed effects Cox model was used for statistical analyses, adjusting for age, sex, marital status, education, race, physical activity, alcohol consumption, smoking, and baseline diseases.
Results: Risk of death increased for those having probable sarcopenia only (hazard ratio [HR]: 1.61, 95% confidence interval [CI]: 1.39-1.85) or probable sarcopenia with obesity (HR: 1.36, 95% CI: 1.13-1.64) but not for the obese-only group (HR: 0.92, 95% CI: 0.85-1.01), when compared to non-obese non-sarcopenic individuals. The results were similar regardless of adjustments for covariates or different obesity criteria applied.
Conclusion: Probable sarcopenia, whether combined with obesity or not, is associated with increased mortality. Obesity did not increase mortality among older adults. Maintaining muscle strength and identifying older adults at risk of sarcopenia is important for the prevention of premature mortality.